FTIR and photoluminescence studies of porous silicon layers oxidized in controlled water vapor conditions - M.A. Vásquez-A. (Revista Mexicana de Física, 2007)
A study is presented on the evolution of the FTIR features and the changes in the photoluminescence (PL) spectra of chemically oxidizedporous silicon layers (PSLs) successively aged under controlled conditions. The PSLs were prepared by the electrochemical method toguarantee uniformity over extended areas. Just after the silicon porification process, the FTIR spectra of the PSLs show silicon-hydrogenbands related to the hydrogen terminated porous silicon surface. As the PSLs oxidized, various vibrational modes were modified. The newobserved vibrational frequencies are related to the defective silicon oxide formed at the porous silicon surface. The room temperature PLspectra of freshly prepared PSLs show a characteristic peak located at »700 nm. The intensity of the PL signal on chemically oxidizedsamples increased by an order of magnitude; afterwards, when the samples were aged in saturated water vapor conditions, the PL spectrawere strongly modified. These changes indicated that the PSL structure is modified by the oxidization processes applied. Analysis of theFTIR data and the behavior of the PL signal enable us to interrelate the quantum size related effects and the formation of some kind of defectin the silicon oxide film over the PSLs. The characteristics of the PSLs reported in this paper are perfectly reproducible in the conditionsused for the sample preparation; therefore, these films can be used in different applications.